Number of Spring-Staging Barnacle Geese - Branta leucopsis (Bechst.) and Species Status in Southern Karelia - Nikolai Lapshin; Alexandr Artemyev; Sergey Simonov (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2016)
The Barnacle Goose used to be a transit migrant in Karelia in the last century, and the size of the East-European population was about tens of thousands of birds on a downward trend. As a result, the Barnacle Goose fell under the protection of the Red Data Book of the Russian Federation. Until the early 2000s, occasional birds were registered at stopovers in Karelia only in the middle of May. However, the bird numbers in the East- European and the Baltic Sea region populations increased in the 2000s, and as a consequence of this growth the capacity of grasslands became insufficient. Transit migrants had to look for new foraging grounds. Nowadays we can see Barnacle Geese in Karelian stopovers starting mid-April, and the bird numbers have been growing steadily. Some Barnacle Goose pairs have lately started to breed in Karelia on the Valaam archipelago islands in Lake Ladoga and at Lake Onego, which means the species has changed the status from "transit migrant" to "local breeder and migration time visitor".